Visualization of phosphorus re‐translocation and phosphate transporter expression profiles in a shortened annual cycle system of poplar. (11th April 2022) - Kurita, Yuko; Kanno, Satomi; Sugita, Ryohei; Hirose, Atsushi; Ohnishi, Miwa; Tezuka, Ayumi; Deguchi, Ayumi; Ishizaki, Kimitsune; Fukaki, Hidehiro; Baba, Kei'ichi; Nagano, Atsushi J.; Tanoi, Keitaro; et al.
Abstract: Phosphorus (P) is an essential macronutrient for plant growth. In deciduous trees, P is remobilized from senescing leaves and stored in perennial tissues during winter for further growth. Annual internal recycling and accumulation of P are considered an important strategy to support the vigorous growth of trees. However, the pathways of seasonal re‐translocation of P and the molecular mechanisms of this transport have not been clarified. Here we show the seasonal P re‐translocation route visualized using real‐time radioisotope imaging and the macro‐ and micro‐autoradiography. We analysed the seasonal re‐translocation P in poplar ( Populus alba . L) cultivated under 'a shortened annual cycle system', which mimicked seasonal phenology in a laboratory. From growing to senescing season, sink tissues of 32 P and/or 33 P shifted from young leaves and the apex to the lower stem and roots. The radioisotope P re‐translocated from a leaf was stored in phloem and xylem parenchyma cells and redistributed to new shoots after dormancy. Seasonal expression profile of phosphate transporters ( PHT1, PHT5 and PHO1 family) was obtained in the same system. Our results reveal the seasonal P re‐translocation routes at the organ and tissue levels and provide a foothold for elucidating its molecular mechanisms. Summary Statement: The phosphorus re‐translocation routes in Populus alba were visualized and gene expression of Pi transporters was analysed, using a shortened annual cycle system. Sink tissues of P shifted from young leaves to the stem and roots during senescence and stored P were reused for next spring growth.